The Prayer Invocations of Adherents of the Mari Ethnic Religion: Forms and Meanings - Lyubov A. Abukayeva (Финно-угорский мир)
Introduction. The spiritual quest of humanity and the reevaluation of the role of religious factors in society, driven by global transformations, necessitate an examination of the distinctive features of religious worldviews. Interdisciplinary research conducted within the frameworks of linguistic culturology, theolinguistics, and religious conceptology enables the analysis of language as a means of recording, preserving, and transmitting the most significant aspects of culture, thereby revealing the essential characteristics of such a unique phenomenon as the Mari ethnic religion. The texts of Mari prayers have not previously been examined as objects of linguistic and culturological inquiry by scholars. The aim of this study is to identify the semantic content of words and constructions expressing devotional invocations in the prayer texts of the Mari ethnic religion.